Characteristics and causal paths of refined oil depot accidents in China: A statistical and network-based analysis - Wei Jiang; Zhuoye Zhang; Shengxiang Ma; Sha Pan; Nannan Sang (PLoS ONE, 2026)
Refined oil depots store large quantities of flammable and explosive substances and involve frequent storage and transfer operations, making them prone to accidents with severe consequences, including casualties, and economic losses. To improve accident prevention in refined oil depots, this study first collected, verified, and cleaned accident records, resulting in a dataset of 470 refined oil depot accidents in China. Accident characteristics were analyzed in terms of accident type, unit, operating status, and causes. Finally, based on accident type characteristics, oil spill-fire and explosion accidents were selected as the focus, a directed accident cause network was constructed by analyzing the influence relationships among accident causes, and UCINET was used to analysis critical causes and paths. The results indicate that accidents occur most frequently in storage units (52.1%) and during loading and unloading operations (67.2%). Oil spill is the most common accident type (36.2%), and operational errors are a prominent cause (20.4%). Based on the propensity of oil spill accidents to trigger fire and explosion accidents, network analysis was conducted to identify critical paths and causes. The results indicate that operational errors, protection defects, and defects of equipment are critical causes, and four critical pathways were identified: inadequate training → operational errors → accidents; inadequate training → operational errors → equipment defects → accidents; inadequate procedures → operational errors → accidents; inadequate procedures → operational errors → equipment defects → accidents. These findings provide support for differentiated safety management and targeted accident prevention strategies in refined oil depots.